PEMERKASAAN TUNTUTAN NAFKAH WANITA: KAJIAN DI MAHKAMAH SYARIAH KOTA BHARU - Mohd Zawawi, Nur Ain Nazifa; Muhammud, Farah Safura (Jurnal 'Ulwan, 2024)
Since covid-19 was spreading in a whole world in 2020, applying for divorce and alimony petition shown increased. According to the record from Department Of Syariah Judiciary Malaysia (JKSM) 6,341 alimony cases was reported along five years. Before pandemic covid-19, only five cases was reported in one month but during pandemic, the alimony cases was increasing to five cases in five day after Family Support Division (BSK) open the online apllication from their officially facebook. However, even the application increasing, there are several women who is suffer from this situation do not take an action to claim their alimony though divorce application always increasing along years by years which is 45,420 cases was reported. Hence, this research to study the factor reluctance of woman to claim their alimony in Syariah Judiciary Kota Bharu, Kelantan. This qualitative research by applying analytical methods of data collection through documents and interviews using thematic methods involving two respondent from Syariah Judiciary Kota Bharu and five respondent women from Kelantan. The research's findings suggest that there is three factor reluctance of women to claim their alimony which is factors of lack of awareness, lack of finance and factor of alimony claim process. Therefore, the research's suggest there is important to empowering woman in matrimonial property. Ignorance and indifference will contribute to the oppression, mistreatment and injustice of women. In conclusion, a prosperous family is the basis for the construction of a Keluarga Madani in line with welfare which is the core value of a Keluarga Madani.